Competition for a preliminary design for the urban restructuring of the Zaragoza city center, 1969 - Martínez Litago, Elena (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
It has been throughout the twentieth century when the area known as "El Tubu" and surrounding area Street of broken and irregular shape, has had a number of different proposals for development by the City of Zaragoza without any come to an end. In the early twentieth century the city of Zaragoza, in part because of its strategic topographical and territorial situation becomes important due to the development of multiple industries with a significant increase in the population and with the intention of turning the Old City into a "modern city". The April 17 of 1909, Antonio Fleta, mayor of Zaragoza, announces a public tender for the project presentation and execution of works for the opening of a street, which starts at the Coso, I finished in the Plaza del Pilar. Means a street which has the extended axis corresponding to the Paseo de la Independencia, and the Martyrs, finished in Pilar. The object of the competition is the presentation of projects while implementing measures necessary for the opening of the street and the buildings that are to constitute it works. In the Official Gazette of the Province of Zaragoza #93, dated Tuesday, April 20, 1909, tender documents Contest drafted by the municipal architect Ricardo Magdalena with deadline for proposals to be published June 22. After which, and in the absence of proposals, the contest was declared void.